STUDI DOSIS RADIASI PADA PEMERIKSAAN COMPUTER TOMOGRAPHY (CT) SCAN DENGAN NILAI COMPUTER TOMOGRAPHY DOSE INDEX (CTDI) DI RUMAH SAKIT BHAYANGKARA MAKASSAR - Irnawati, Irnawati (JFT : Jurnal Fisika dan Terapannya, 2018)
This research aims to determine the radiation dose received by patients on a CT-Scan examination using the CTDI value and to determine whether the dose received by the patient is in accordance with the dosage standard issued by the Nuclear Energy Supervisory Agency (BAPETEN) and uses the piranha X-Ray Multimeter on Different voltage and slice thickness, namely at a voltage of 100 kV, 120 kV, 135 kV. And the slice thickness is 2 mm, 4 mm, and 10 mm, and the tube current and scanning time are constant, namely 100 mA and 1 s. Where the measurement is carried out in 2 stages, namely the first stage measuring the CT-Scan radiation dose with the CTDI value in the air and the second stage measuring the CT-Scan radiation dose with the CTDI value on the phantom. The results showed that the highest dose received for CTDI in the air was at a voltage of 135 kV at a thickness of 10 mm, namely 49.656 mGy, the lowest value for CTDI in air was at a voltage of 100 kV at a thickness of 2 mm, namely 28.771 mGy. While the highest CTDI value on the Phantom is at a voltage of 135 kV at a thickness of 10 mm, namely 41.749 mGy, the lowest CTDI value on the phantom is at a voltage of 100 kV at a thickness of 2 mm which is 15.819 mGy. This is in accordance with the provisions of BAPETEN, namely the dose value received does not exceed 50 mGy for CT-Scan examination.